PROFIL SOSIAL EKONOMI MASYARAKAT NELAYAN DI KELURAHAN BARAS KECAMATAN BARAS KABUPATEN PASANGKAYU PROVINSI SULAWESI BARAT - Ardila; Eko Sugiharto; Elly Purnamasari (2339-1324, 2019)
This study aims to determine the social profile of fishing communities from the aspects of social systems, client patrons, social relations, social characteristics and cultural characteristics and to know the economic profile of fishing communities from the aspects of acceptance from the main and side jobs. The study was conducted based on descriptive data collection methods to obtain a factual and concrete picture of the profile of the socio-economic community of fishermen in Baras Sub-District, Baras District, Pasangkayu Regency and the data was then processed and analyzed in qualitative and quantitative descriptive ways. The results of the study showed that the fishing community groups in the Baras Village generally lived in the coastal areas near the daily activities. They depend on changing / unpredictable natural conditions. Charasteristics of fishermen in Baras Village is of low education level where the majority of elementary school graduates and part of the tammatan junior high school are predominantly Muslim and have Mandar tribes. Their business experience in the fisheries sector is 10-35 years. The results showed that the acceptance of fishing communities in the Baras Sub-District, Baras District, Pasangkayu Regency was Rp. 291,600,000.00 / KK / Year with an average of Rp. 29,160,000.00 / KK